Analisis Korelasi antara Intensitas Mengakses Media Sosial dengan Persepsi tentang Puisi “Doa Yang Ditukar” pada Anggota Mahasiswa Nahdlatul Ulama (KMNU) UIN Sunan Kalijaga Yogyakarta - Faiz, Achmad Zaky (Jurnal Studi Jurnalistik, 2022)
This article aims to determine the relationship between the intensity of access to social media with students' perceptions of the Poetry "Doa yang Ditukar." This research uses the Stimulus-Organism-Response (S-O-R) theory, examining the correlation between stimulus exposure and objects' responses. In addition, this research also uses a survey method on 115 students of the Nadhatul Ulama community at the UIN Sunan Kalijaga Jogja Campus. The results of hypothesis testing with Pearson's Product Moment Correlation show a correlation score of 0.338 with p = 0.000 (p > 0.05), which means that there is a significant relationship in low level between the access intensity of social media and perceptions of poetry.